Stock Market Prize Prediction Using Linear Regression and Spring XD Framework - S., M Prabin; M., S Thanabal (International Journal of Psychosocial Rehabilitation, 2020)
Huge data in a continuous manner is required for prediction in the stock market. This research work proposes a linear regression-based prediction model for real-time data analysis. The data pipelining technique is employed that provides the data to the regression model for prediction. This work focuses on the stock prediction from APPLE, Amazon, and Google sources and, in the future, can be extended for multiple stocks. The spring XD framework was used for the pipeline of data, and four different prediction models are employed in this work. The outcome of this work can be used for real-time stock price prediction.